Direct Conversion Receiver - Wan Khairuddin, Wan Nur Hafsha (Universiti Sains Malaysia, 2005)
Direct conversion receiver is a receiver system that is widely used for wireless communication. Direct conversion receiver replaced the architecture of superheterodyne receiver. The objectives of my project is to do analysis of IQ Demodulator IC model LT5516 produced by Linear Technology and also the analysis of direct conversion receiver system using LT5516 to see the performance of this receiver. The test circuit for LT5516 is designed using printed circuit board (PCB). Narrowband balun structure is designed for input of RF signal and LO signal. Air core inductor is used for balun design. The analysis of LT5516 cannot be done because the connection between the LT5516 pads and printed circuit board cannot be done so that the test circuit cannot function without the connection of this LT5516 IC.The LT5516 IC cannot be soldered on printed circuit board because the size of the IC is too small (4mmx4mm). The soldering method used is not effective but I still used this method because there are no other technology in this campus. LT5516 pads are connected to printed circuit board using wire-wrap as the conductor. Wire-wrap is soldered to LT5516 pads and connected to PCB pads but lastly IC LT5516 cannot be soldered on PCB because the IC pads are small and resulted the soldering joint. To solve this problem I decreased the amount of solder but the wire wrap could not stick on IC pads. Other components are soldered on PCB pads but the analysis still cannot be done without this IC LT5516. Aluminium box is designed for this test circuit .The aluminium box is designed to avoid radiation that will effect the output signal. The calculation for band pass filter and low pass filter are include in this report even they cannot be applied because the circuit not function and cannot be analyze. The suggestions also include at the end of the report to ensure that the direct conversion receiver can function well and can be analyze to see the performance of direct conversion receiver.